Atypical presentation of very aggressive ALK-Negative Primary CNS Burkitt’s Lymphoma in a Child: A Rare Case Report - Miriyala, Chandan; Patil, Abhishek; Gautam, Abhishek; S, Abhilasha.; B. N, Nandeesh (Journal of Neonatal Surgery, 2025)
Primary central nervous system (CNS) lymphoma is exceptionally rare in paediatric populations, being particularly unusual when they present with abdominal symptoms. This case report describes a nine-year-old patient with atypical presentation of this aggressive malignancy. A nine-year-old child, born of a second-degree consanguineous marriage with low birth weight (1.5 kg), presented with a 10-day history of diffuse abdominal pain with vomitings. Physical examination revealed multiple congenital anomalies including bifid tongue, tongue tie, dermatological findings included café au lait spots (midline and left buttocks), hypopigmented patches suggestive of vitiligo on the left knee, and diffuse hyperpigmented dry skin. Subsequent evaluation led to the diagnosis of ALK-negative primary CNS Burkitt’s lymphoma, a rare entity in paediatric patients. This case highlights the importance of considering primary CNS Burkitt’s lymphoma in the differential diagnosis of paediatric patients presenting with nonspecific symptoms and neurological findings, particularly in the context of congenital anomalies that might suggest underlying genetic predisposition. The atypical presentation underscores the need for heightened clinical suspicion and comprehensive diagnostic workup in similar cases very early and start the child on chemotherapy so that aggressive tumour can be treated.